Development of Augmented Reality-Based English Learning Media for Vocabulary and Pronunciation - Hadi, Said Hirzi (JEECS (Journal of Electrical Engineering and Computer Sciences), 2025)
English learning at the junior high school level often faces challenges in improving vocabulary mastery and pronunciation skills. Previous studies have demonstrated the effectiveness of Augmented Reality (AR) in supporting language learning. However, most of these studies focused only on vocabulary acquisition without integrating pronunciation practice or contextualized 3D object interaction. Therefore, this study aims to develop an AR-based learning medium that visualizes household objects such as refrigerators, microwaves, and scissors, accompanied by their pronunciation sounds. The application was developed using Unity and Vuforia SDK and tested through Black Box Testing and the System Usability Scale (SUS). The test results indicate that the system functions properly and obtained an SUS score of 82.5, categorized as “Excellent.” The developed media is expected to enhance students’ English vocabulary and pronunciation skills through an interactive and enjoyable learning experience that bridges the existing gap in AR-based English learning.